2002
DOI: 10.1016/s0896-6273(02)01026-7
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Role for a MEK-C/EBP Pathway during Growth Factor-Regulated Cortical Neurogenesis

Abstract: Mammalian neurogenesis is determined by an interplay between intrinsic genetic mechanisms and extrinsic cues such as growth factors. Here we have defined a signaling cascade, a MEK-C/EBP pathway, that is essential for cortical progenitor cells to become postmitotic neurons. Inhibition of MEK or of the C/EBP family of transcription factors inhibits neurogenesis while expression of a C/EBPbeta mutant that is a phosphorylation-mimic at a MEK-Rsk site enhances neurogenesis. C/EBP mediates this positive effect by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
183
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(198 citation statements)
references
References 41 publications
14
183
0
1
Order By: Relevance
“…6,7 In addition to its effects on general transcriptional potency, MEK-dependent phosphorylation of C/EBPb at Thr 188 biases cortical progenitors towards a neuronal fate in the developing CNS. 10,11 Although it is not yet known whether stress-induced MKP-1 antagonizes the pro-survival function of C/EBPb in the injured adult nervous system, we found that loss of C/EBPb expression in hypoxic neurons promotes cell death in vitro, 12 suggesting the stoichiometric relationship between the available pool of bZIP heterodimeric partners particularly important. 12,13 In the present study, we test the hypothesis that MKP-1 serves a molecular switch, exerting similar suppressive effects on the pro-survival factor C/EBPb following ischemic injury as has previously been described for HIF-1a.…”
mentioning
confidence: 73%
“…6,7 In addition to its effects on general transcriptional potency, MEK-dependent phosphorylation of C/EBPb at Thr 188 biases cortical progenitors towards a neuronal fate in the developing CNS. 10,11 Although it is not yet known whether stress-induced MKP-1 antagonizes the pro-survival function of C/EBPb in the injured adult nervous system, we found that loss of C/EBPb expression in hypoxic neurons promotes cell death in vitro, 12 suggesting the stoichiometric relationship between the available pool of bZIP heterodimeric partners particularly important. 12,13 In the present study, we test the hypothesis that MKP-1 serves a molecular switch, exerting similar suppressive effects on the pro-survival factor C/EBPb following ischemic injury as has previously been described for HIF-1a.…”
mentioning
confidence: 73%
“…During development, c/EBP-β signaling biases precursor cells to commit to a neural rather than glial lineage (Menard et al, 2002). c/EBP-β activity also induces axonal sprouting after axotomy, and, not surprising, regulates the expression of the neuronal markers NeuN, GAP43 and βIII tubulin (Nadeau et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This domain consists of a basic region, contacting DNA, and a homo-or heterodimer-forming region called the leucine zipper (9). Because of the high conservation in the bZIP domain, C/EBP family members are able to form homo-or heterodimers, and all, except C/EBP , bind to the same cis-regulatory elements.C/EBP␣, C/EBP␤, and C/EBP␦ are involved in terminal differentiation of a variety of cells including adipocytes (10), hepatocytes (11,12), gut epithelial cells (13), macrophages (14), myelomonocytes (15), and neurons (16,17). In the nervous system, the role of C/EBP family members is not characterized as well as, for instance, in adipocytes or hepatocytes.…”
mentioning
confidence: 99%
“…C/EBP␣, C/EBP␤, and C/EBP␦ are involved in terminal differentiation of a variety of cells including adipocytes (10), hepatocytes (11,12), gut epithelial cells (13), macrophages (14), myelomonocytes (15), and neurons (16,17). In the nervous system, the role of C/EBP family members is not characterized as well as, for instance, in adipocytes or hepatocytes.…”
mentioning
confidence: 99%
See 1 more Smart Citation